Pengaruh Transparansi dan Akuntabilitas Pengelolaan Keuangan terhadap Kinerja Kepala Sekolah dengan Partisipasi Anggaran sebagai Variabel Intervening (Studi pada SMAN di Kabupaten Wajo) - Saleh, Andi Mulia (Patria Artha University, 2017)
ABSTRACTThis reseacrh conducted with the aim to (1) to test and analisys the influence of financial management transparency and accountability towards the performance of school headmaster and the budget participation as the intervening variable at SMAN in Wajo regency. This research used the quantitative approach. The place of research conduted to 15 SMAN in Wajo regencyby distributing questionnaire amount 180 copies to respondents as population. Sample selected by using the solution sampling consideringthe respondent has already worked for two years. The questionnaire used likers scale. The method of analysis used path analysis. Hypothesis test used significance level a = 0.05. the obtained data then proceeded by using SPSS 15. The results of desriptive analysis showed that transparency, accountability, budget participation, and the performance of school principal existed in high category. The result of hypothesis test showed the direct positive and signifiant influence between transparency and accountability towards the performance between tranparency and acountability towards the indiret positive influence between transpsrency and accountability towards the performance of school headmaster with the budget participation as the intervening variable.